2015
DOI: 10.1093/mnras/stv1354
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Downsizing model – III. Planets from sub-Earths to brown dwarfs: structure and metallicity preferences

Abstract: We present population synthesis calculations of the Tidal Downsizing (TD) hypothesis for planet formation. Our models address the following observations: (i) most abundant planets being Super Earths; (ii) cores more massive than ∼ 5 − 15M ⊕ are enveloped by massive atmospheres; (iii) the frequency of occurrence of close-in gas giant planets correlates strongly with metallicity of the host star; (iv) no such correlation is found for sub-Neptune planets; (v) presence of massive cores in giant planets; (vi) gas g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(117 citation statements)
references
References 117 publications
(191 reference statements)
7
110
0
Order By: Relevance
“…This behaviour is distinctly different from that of the well know hot Jupiter population (Fischer & Valenti 2005). Disc fragmentation followed by rapid migration of gas clumps in fact predicted (Nayakshin & Fletcher 2015) that planets with mass greater than ∼5 M J and brown dwarfs will not correlate with metallicity of the host star (see also sections 9.4 and 9.5 of Nayakshin 2017). Therefore, the most natural interpretation of these observations is that at least some of the objects made by disc fragmentation at separations of ∼100 au did migrate in, and in fact all the way to separations of ∼0.1 − 1 au.…”
Section: On the Origin Of Disagreement With Models By Forgan And Ricementioning
confidence: 83%
See 1 more Smart Citation
“…This behaviour is distinctly different from that of the well know hot Jupiter population (Fischer & Valenti 2005). Disc fragmentation followed by rapid migration of gas clumps in fact predicted (Nayakshin & Fletcher 2015) that planets with mass greater than ∼5 M J and brown dwarfs will not correlate with metallicity of the host star (see also sections 9.4 and 9.5 of Nayakshin 2017). Therefore, the most natural interpretation of these observations is that at least some of the objects made by disc fragmentation at separations of ∼100 au did migrate in, and in fact all the way to separations of ∼0.1 − 1 au.…”
Section: On the Origin Of Disagreement With Models By Forgan And Ricementioning
confidence: 83%
“…initial disc masses and sizes, exact masses of the fragments, migration rates and switch-over conditions from type I to type II, rates of gas accretion on to the planets, dust opacity and grain sedimentation physics -may lead to widely different conclusions. For example, population synthesis of Nayakshin & Fletcher (2015) and Nayakshin (2016) predicts that only ∼5 per cent of gas clumps born at wide separations survive there by the age of a few Million years when the disc is dispersed, in stark contrast to the results of Forgan & Rice (2013b).…”
Section: Hypothesis I: Fragmentation Of Discs On Planet Mass Clumps Imentioning
confidence: 98%
“…Figure 18 shows the host star metallicity distribution for gas giants with mass 0.3 M J < M p < 5 M J from population synthesis of Nayakshin & Fletcher (2015) with the blue filled histogram. Only planets that end up at separations less than 5 AU are shown in the figure.…”
Section: Moderately Massive Gas Giantsmentioning
confidence: 99%
“…Based on planet population synthesis, Mordasini et al (2009) showed that the core-accretion mechanism proposed for giant planet formation may produce planets not only more massive than 13M Jup , i.e., above the deuterium burning limit (Burrows et al 2001), but also in the 20-40M Jup range. Based on population synthesis calculations of the tidal downsizing hypothesis, Nayakshin & Fletcher (2015) recently suggested that gravitational instability -proposed as an additional formation mechanism to the most natural one for BDs (via molecular cloud fragmentation)-can also lead to the formation of giant planets.…”
Section: The Sample Of Brown Dwarfs Transiting Main Sequence Starsmentioning
confidence: 99%